Complete Genome Sequence of Corynebacterium pseudotuberculosis Strain Cp267, Isolated from a Llama - Lopes, Thiago (American Society for Microbiology, 2012)
In this work we report the genome of Corynebacterium pseudotuberculosis strain 267, isolated from a llama. This pathogen is of great veterinary and economic importance, as it is the cause of caseous lymphadenitis in several livestock species around the world and causes significant losses due to the high cost of treatment.